6-Pyruvoyltetrahydropterin synthase deficiency: review and report of 28 Arab subjects - Almannai, Mohammed; Blau, Nenad (Pediatric neurology, 2019)
BACKGROUND: Tetrahydrobiopterin is an essential cofactor for the hydroxylation of aromatic amino acids phenylalanine, tyrosine, and tryptophan. Therefore, tetrahydrobiopterin deficiency results in hyperphenylalaninemia as well as dopamine and serotonin depletion in the central nervous system. The enzyme 6-pyruvoyltetrahydropterin synthase catalyzes the second step of de novo synthesis of tetrahydrobiopterin, and its deficiency is the most frequent cause of tetrahydrobiopterin metabolism disorders. - METHOD: We conducted a retrospective chart review of 28 subjects from 24 families with molecularly confirmed 6-pyruvoyltetrahydropterin synthase deficiency from six centers in three Arab countries. We reviewed clinical, biochemical, and molecular data. We also reviewed previously published cohorts of subjects with 6-pyruvoyltetrahydropterin synthase deficiency. - RESULTS: Similar to previous observations, we show that early treatment (less than two months) is associated with better outcome. We identify eight PTS variants in 24 independent families. The most common variant is (c.238A>G; p.M80V) with an allele count of 33%. We also identify one novel variant (c.2T>G; p.?). - CONCLUSION: The deficiency of 6-pyruvoyltetrahydropterin synthase is relatively common in the Arab population and should be considered in individuals with hyperphenylalaninemia. More natural history studies with comprehensive biochemical and molecular genetics data are needed for a robust base for the development of future therapy.